2001
DOI: 10.1086/319746
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Etiology of Community-Acquired Pneumonia in the Adult Population of 4 Municipalities in Eastern Finland

Abstract: To determine the etiology of community-acquired pneumonia in the adult population of a defined area, specific antibody responses in paired serum samples, levels of circulating pneumococcal immune complexes in serum samples, and pneumococcal antigen in urine were measured. Samples (304 paired serum samples and 300 acute urine samples) were obtained from 345 patients > or =15 years old with community-acquired, radiologically confirmed pneumonia, which comprised all cases in the population of 4 municipalities in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
117
3
4

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(137 citation statements)
references
References 53 publications
13
117
3
4
Order By: Relevance
“…The results of this study also support the high incidence of CAP caused by atypical pathogens reported by other investigators (12)(13)(14). In our cohort, evidence of acute infection with an atypical organism was found in 20% of patients with CAP and in Ͼ40% of the cases with an etiologic diagnosis.…”
supporting
confidence: 92%
“…The results of this study also support the high incidence of CAP caused by atypical pathogens reported by other investigators (12)(13)(14). In our cohort, evidence of acute infection with an atypical organism was found in 20% of patients with CAP and in Ͼ40% of the cases with an etiologic diagnosis.…”
supporting
confidence: 92%
“…These include S. pneumoniae, M. pneumoniae, H. infl uenzae, Chlamydia species, Legionella species, Staphylococcus aureus, and respiratory viruses (infl uenza, respiratory syncytial virus [RSV], adenovirus, parainfl uenza) (6,23,24). In this study, only 6% of hospital admissions had a specifi c pathogen identifi ed in the primary diagnostic code.…”
Section: Discussionmentioning
confidence: 99%
“…Legionella organisms may vary in importance in different countries [46,62], although this is not shown clearly from prospective studies, partly because of the infrequency of studies from countries where the organism is thought to be uncommon and by other studies in what might be local "hot spots" for legionella infection which may not represent the country as a whole [47,48,67]. There is a perception that the Legionella organism is more important in Mediterranean countries [62], and is uncommon in Northern European countries, other than in travellers from these areas or in the context of a local source of infection.…”
Section: Causative Pathogensmentioning
confidence: 99%
“…burnetii is a rare cause of CAP. There does appear to be geographic variation in frequency, with the organism virtually absent in some parts of Scandinavia [46], but second only to S. pneumoniae as a cause in e.g. North West Spain [68].…”
Section: Causative Pathogensmentioning
confidence: 99%